Ski-snow friction determined with a novel ski-snow tribometer - Schindelwig, K. (1. Snowstorm Konferenz, 2017)
The friction of skis on snow is influenced by a variety of factors: e.g. speed, contact area, snow type (temperature, liquid-water content, hardness, texture), and ski properties (stiff-ness, thermal conductivity, base material, base roughness) (Nachbauer et al., 1996). A novel linear tribometer was developed allowing studies with whole skis at sport specific speeds. The Carriage's speed can be set between 0.1 and 30 ms-1. The runway of the carriage is 24 m long. The trough for snow or ice can be moved laterally in order to allow several runs on a fresh snow surface. The vertical force can be varied between 50 and 700 N. The tribometer is located in a cooling chamber with a lower air temperature limit of -20°C. The precision of the tribometer was better than 2.2% (Hasler et al., 2016). This precision is high enough for discriminating differences needed for the analysis of different ski and snow conditions and the study of friction processes. In the following, examples using the tribometer to improve the knowledge of ski-snow-ski friction are presented: Schindelwig et al. (2014) determined the temperature below a gliding cross country ski with infrared sensors at four positions and three different velocities. Friction coefficient, pressure distribution and temperature measurements showed a high reliability and allowed to create a model to explain the temperature profile along the ski. Rohm et al. (2015) investigated the effect of the surface structure on the friction between steel and snow. The friction tests showed that the surface roughness had a major effect on friction between steel and snow, with higher friction for smooth surfaces than for rough ones. Nachbauer et al. (2016) analysed the friction along a slider on snow. The local coefficient of friction along the slider revealed high friction in the front part, considerably lower one in the second segment, constant or slightly increased one in the middle part, and towards the end increased friction. This may be attributed to dry friction in the front part, subsequently smaller friction due to lubrication by meltwater and finally increased capillary drag towards the end. Rohm et al. (2016) analysed the effect of surfaces with different bearing ratios, but similar roughness heights, on the friction between ultrahigh molecular weight polyethylene (UHMWPE) and snow. The friction tests showed that the bearing ratio had a major effect on the friction between UHMWPE and snow. For temperatures close to the melting point a surface with wide grooves and narrow plateaus (nonbearing surface) performed well. For cold conditions, the friction was less for a surface with narrow grooves and wide plateaus (bearing surface).